The evolution of FLASH radiotherapy: a bibliometric analysis - Jia, Shuokai; Wei, Weige; He, Yiwen; Yan, Haichuan; Zou, Shiru; Hao, Yanmei; Xiao, Qing; Li, Guangjun (Frontiers in Oncology, 2025)
IntroductionFLASH radiotherapy (FLASH-RT) represents a groundbreaking technique, characterized by its ultra-high dose rate and its remarkable ability to spare normal tissues from damage. Numerous studies on FLASH-RT have been conducted worldwide. However, to date, no comprehensive bibliometric analysis has been performed in this field. This study aims to provide an overview of the advancements in FLASH-RT and identify potential future research directions through bibliometric analysis.Method and materialsThe research team performed a literature search in the Web of Science Core Collection (WOSCC), covering the period from 1967 to 2024, and identified 461 publications relevant to the field of interest. Visualization tools, including VOSviewer, CiteSpace, and Bibliometrix, were employed to analyze countries, institutions, authors, journals, references, and keywords, thereby uncovering research frontiers and hotspots within the field.ResultsIn recent years, a considerable number of publications on FLASH-RT have emerged. The United States has the highest number of publications (n=208). The institution with the highest publication count is “Lausanne University Hospital” (n=39). The author with the most citations is “Vozenin, M” (n=31), while the author with the most co-citations is “Montay-Gruel, P” (n=812). Medical Physics is the journal with the highest number of both publications and co-citations, whereas Radiotherapy and Oncology has the highest number of citations. The paper titled “Ultrahigh dose-rate FLASH irradiation increases the differential response between normal and tumor tissue in mice” has the highest number of both citations and co-citations. The most frequently co-occurring keywords is “FLASH radiotherapy” (n=379).ConclusionsOur bibliometric analysis of FLASH-RT explores key dimensions of the field, including publication trends, international collaborations, influential journals and authors, and keyword evolution. It assesses FLASH-RT’s historical development, current global status, and recent progress in biological mechanisms, equipment, and clinical translation, aiming to offer researchers a comprehensive overview.